Pengaruh Kualitas Pelayanan dan Harga terhadap Kepuasan Konsumen pada Toko Jakmart di PD. Pasar Jaya Kendari - Hasan, Mohamad Aldi; Pasaribu, Veta Lidya Delimah (BUDGETING : Journal of Business, Management and Accounting, 2024)
This research aims to determine "The Influence of Service Quality and Price on Consumer Satisfaction at Jakmart Stores in Pd. Pasar Jaya Kenari”. This type of research was quantitative research that was associative in nature used data collection techniques through distributied questionnaires which were distributed to 89 respondents. The method used to test and analyze the influence partially and simultaneously is by used regression analysis, correlation coefficient, coefficient of determinated, t test and f test. Testing the service quality hypothesis (X1) obtained a t value of 8.567 > t table 1.663 and a significant level of 0.000 < 0.05, thus Ho was rejected and Ha was accepted, meaning that partially the service quality variable has a significant effect on Consumer Satisfaction. Testing the price hypothesis (X2) obtained a t value of 10.220 > t table 1.663 and a significant level of 0.000 < 0.05, thus Ho was rejected and Ha was accepted, meaning that partially there was a significant influence of the price variable on Consumer Satisfaction. Simultaneous test results for all variables show an Fcount value of 59.124 with a significance level of 0.000 while the Ftable is 3.101. Thus Fcount 59.124 > Ftable 3.101 and significance 0.000 < 0.05. Thus Ha was accepted and Ho was rejected. This means that the hypothesis states that the variables of service quality and price together (simultaneously) have a significant influence on Consumer Satisfaction. The coefficient of determination of the influence of the Service Quality (X1) and Price (X2) variables on Consumer Satisfaction (Y) is 0.579 or 57.9%. Meanwhile, the remaining 42.1% is influenced by other variables, outside this research. Keywords: Consumer Satisfaction, Price, Service Quality.